O diagnóstico clínico a partir da anamnese e exame físico para acadêmicos da Faculdade de Medicina - Schaefer, Bárbara Freiberger (2018)
Introduction: The medical interview is fundamental for the approximation and recognition of the patient, and the physical examination usually increases the diagnostic possibility in the investigation. Technological development and immense diagnostic possibilities through complementary examinations have led to the idea of lesser importance of anamnesis and physical examination. Objective: To evaluate the undergraduate medical student's ability to perform a correct clinical diagnosis, from the presentation of clinical cases with information only from anamnesis or anamnesis and clinical examination together, without complementary exams. Methodology: A cross-sectional, exploratory study with quantitative data analysis of four clinical cases (two with isolated anamnesis and two with anamnesis and physical examination) answered by the students as a teaching task of the Medical Clinic discipline, with 97 academics from the School of Medicine of PUCRS from 2016 to 2017. Results: The findings showed that the majority of the students who participated in the study were female (54 subjects - 55.7%), predominantly white (94 - 96.9%), on average of 24.1 (+ 2.3) years old, having correctly determined 177 diagnoses (45.62%) in the first hypothesis. There was a significant difference (p <0.001) when compared the number of correct diagnosis in clinical cases with isolated anamnesis 108 (55.6%) to those with anamnesis and physical examination 69 (35.6%). Conclusion: It was verified that, for the undergraduate medical students of the fourth year from the School of Medicine, the correct answers in the first diagnosis were more frequent and with statistical significance, when clinical cases with isolated anamnesis were offered than when it was offered anamnesis and physical examination.